Pengaruh Harga Dan Kualitas Pelayanan Islami Terhadap Kepuasan Pelanggan Pada Bengkel Anugrah Motor - Arum, Dwi Purnama; Suryaningsih, Sri Abidah (Journal Creative Economics and Trading Halal Ecosystem, 2025)
This study aims to identify the influence of prices and Islamic service quality on customer satisfaction at Anugah Motor workshop. This study used a quantitative method with regression analysis using the SPSS 25 version. The instrument used questionnaires and they were distributed to 100 respondents. The determination of the respondents used a purpose sampling technique. The distribution of the questionnaire was carried out both online and offline. Respondents' answers were measured using a Likert scale. The results of the analysis showed that partially, the price variable did not have a positive and significant influence on customer satisfaction. Besides, the Islamic service quality variable partially had a positive and significant influence on customer satisfaction. Simultaneously, the price and Islamic service quality variables had a positive and significant influence on customer satisfaction